Pemanfaatan Canva Sebagai Media Pembelajaran Kelas V SBDP di SD Negeri Hargotirto Kokap Kulon Progo - Arif sabekti; Adhitya Mahendra Pradana (Reflection : Islamic Education Journal, 2024)
The Canva application is a support in the process of creating learning media, which allows the Canva application to develop electronic learning media. The research problem formulation is: (1) Utilization of the SBdP learning environment using the Canva SDN Hargotirto application. (2) How effective is the SBdP learning media with the Canva SDN Hargotirton application. Research is used as a research method whose aim is to describe and analyze phenomena, events, activities, social, attitudes, culture, perceptions, human thoughts individually and in groups. Guided qualitative research, that is, problems arising from the material remain open to the researcher. The subject of this research is Class V of Hargotirto Kokap Kulon Progo State Elementary School. This research tool uses interviews, questionnaires and test questions. This data is then analyzed using a percentage formula. The results of the research produced electronic media planning, namely. requirements analysis, planning, validation and review, and testing and implementation. The performance test results obtained through media expert validation were 95.38% in the very suitable category, 98% in the material category in the very suitable category, 92.31% of the students' tests answered very suitable, then the post-test results. with classic percentages. 100% falls into the very good category. Therefore, using the Canva application as an electronic learning tool is very suitable for increasing the interest of fifth grade students at SD Negeri Hargotirto Kokap Kulon Progo in fine arts.